2021
DOI: 10.1097/aud.0000000000000999
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Daily Device Use and Early Communication Outcomes in Young Children With Cochlear Implants

Abstract: Objectives: Children with significant hearing loss can gain access to sound via a cochlear implant (CI), but they must wear the device to reap the communication benefits of the device. That is, poor daily device use may result in underdeveloped perceptual and language skills in children and adolescents using CIs. This retrospective study focuses on the relationship between daily CI use and communication performance (auditory skills, speech recognition, expressive and receptive language) in young ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…Wiseman, on the other hand, reported a strong relationship between daily device use and early communication. The authors suggested that intervention strategies must also consider barriers to consistent device use and insisted on support for young children with CIs who struggle with inconsistent device use [ 27 ]. Karltorp et al investigated children implanted between 5 and 11 months of age and showed an age-equivalent level of language understanding and improved vocabulary outcomes, which was earlier than when compared to children implanted between 12 and 29 months [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wiseman, on the other hand, reported a strong relationship between daily device use and early communication. The authors suggested that intervention strategies must also consider barriers to consistent device use and insisted on support for young children with CIs who struggle with inconsistent device use [ 27 ]. Karltorp et al investigated children implanted between 5 and 11 months of age and showed an age-equivalent level of language understanding and improved vocabulary outcomes, which was earlier than when compared to children implanted between 12 and 29 months [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that significantly poorer device use is accompanied with demographic factors such as younger chronologic age, lower maternal education, presence of additional disability, and even sign-focused communication mode, etc. [ 27 , 31 , 51 ]. The authors investigated factors in addition to older age at implantation, such as satisfaction with the external component in analyzing the BTE and SU processors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Audiometric and medical criteria provide guidance for when to discuss pediatric implantation, but the CI team also should take a holistic approach considering the family’s lifestyle, goals, and expectations for the child (Moeller 2000; Moeller et al 2013; Dettman et al 2016b). Nonaudiologic factors such as the child and family’s quality of life, availability of resources, history of family involvement, assurance of consistent device use during all waking hours, and realistic expectations afford a well-rounded perspective of a child’s prognosis for CI outcomes (Moeller 2000; Nikolopoulos et al 2004; O’Brien et al 2010; Park et al 2019a; Wiseman et al 2021).…”
Section: Candidacy Considerationsmentioning
confidence: 99%